PKM KARYA TULIS ILMIAH BAGI GURU SMAN 3 ENREKANG DI KECAMATAN ALLA KABUPATEN ENREKANG - Muhammad Hamzah Syahruddin; Amiruddin; Sakka; Hasniati (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2022)
Scientific writing for teachers is one of the requirements to obtain an educator certificate according to the Minister of Administrative Reform Number and the Joint Minister of National Education Regulation and Head of State Staff a teacher must have skills in writing scientific papers. Partners in the PPMU-PKM activities Scientific Writing for teachers isSMAN 3 Enrekang. The problem faced by partners is when there are those who want to take care of certification or take care of promotions, generally constrained by the requirements of scientific papers, because most teachers do not have the skills and ability to write scientific papers. The government's is requiring scientific papers in certification and promotion are encouraging teachers to write scientific papers, Upgrade the work ethic of the teaching profession, and developing one's abilities through research. The ctivity is to provide training in writing scientific papers for partner teachers, with the main target being teachers who are civil servants who will take up promotions or who will take care of teacher certification. The results of this dedication give the ability of the Teacher of SMAN 3 Enrekang to write scientific papers in writing the opening section, the content section, and the closing section and are able to browse online reference sources. --- Karya tulis ilmiah menurut KBBI merupakan karya tulis yang dibuat menggunakan prinsip-prinsip ilmiah dan berdasarkan fakta. Karya tulis ilmiah (KTI) salah satu persyaratan untuk memperoleh sertifikat pendidik. Tulisan ilmiah juga menjadi syarat untuk mengurus kenaikan pangkat dan jabatan fungsional bagi guru. Peraturan Menteri Pendayagunaan Aparatur Negara, dan Peraturan Bersama Mendiknas dan Kepala Kepegawaian Negara mensyaratkan seorang guru harus memiliki keterampilan dalam menulis karya tulis ilmiah. Pada khususnya guru SMU 3 Alla ketika mereka ingin mengurus sertifikasi atau mengurus kenaikan pangkat terkendala dengan persyaratan karya tulis ilmiah. Oleh karena itu tim pengabdian PPMU-PKM Unhas melakukan pelatihan penulisan karya tulis ilmiah. Mitra dalam kegiatan PPMU-PKM adalah Kepala Sekolah SMA Negeri 3 Enrekang Kecamatan Alla Kabupaten Enrekang. Pelatihan dilakukan untuk meningkatkan kemampuan para guru untuk menulis karya tulis ilmiah, menumbuhkan etos kerja profesi guru, dan mengembangkan kemampuan diri melalui penelitian ilmiah. Pelatihan ini Guru SMAN 3 Enrekang mencapai 80 % dapat menuliskan bagian pembuka, bagian isi, dan bagian penutup serta mampu menelusuri sumber-sumber referensi secara online yang dapat dijadikan rujukan.